(untitled) (Asian Education Studies, 2020)
This paper addresses challenges that arose during the on-going coronavirus pandemic and methodologies implemented in teaching a Biomechanics course in the Biomedical Engineering program (Biomedical and Electrical Engineering Discipline, Faculty of Engineering, RMIT University, Melbourne, Australia). We aimed to address thee requirements for a quick transition of thee entire curriculum to efficient remote delivery of the course, which involved: (i) providing authentic learning experiences; (ii) keeping students motivated and engaged with their classes and team projects; and (iii) preventing students from cheating when completing online asessmments. The specific tools, software packages and approaches employed to support the remote teaching and learning are presented and discussed in this paper. Effective and on-going communication with students was crucial for managing their expectations, engagement with the course materials and teaching team, retaining positive learning experiences and for their overall well-being. The Socratic approach used in developing the online assessments was able to promote students’ critical thinking, problem solving and self-reflection and assisted the teaching team in minimising online cheating.